2017
DOI: 10.1002/rcm.7906
|View full text |Cite
|
Sign up to set email alerts
|

A novel rapid analysis using mass spectrometry to evaluate downstream refolding of recombinant human insulin-like growth factor-1 (mecasermin)

Abstract: ESI-IMS-MS coupled with SEC-mode HPLC is a rapid and robust method for analyzing the free-SH:protein ratio of mecasermin that allows proteoform changes to be evaluated and monitored during the oxidation of mecasermin. ESI-IMS-MS is applicable as a process analytical technology tool for identifying the "critical quality attributes" and implementing "quality by design" for manufacturing mecasermin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…1.5 g/l for 50 kDa proteinAnalyze and quantify a mixture of proteoforms during folding (e.g. different disulfide bonds)Expensive equipmentInvolatile sample buffers are not compatible with ESI–IMS–MSFuruki et al (2017)Young et al (2016)Extrinsic fluorescenceTertiary and quaternary structureCa. 0.015 g/l for 50 kDa proteinSensitiveSuitable for high-throughput screeningDye might interfere with protein aggregationHawe et al (2008)Younan and Viles (2015)Fourier transform infrared spectroscopy (ATR-FTIR)Secondary structure and dynamics> 0.01 g/lTolerant to salt and sample turbidityCan be used for all proteinsHigh wavelength precisionNo time-related dataPathak et al (2016)Walther et al (2014)Baldassarre and Barth (2014)Nuclear magnetic resonance spectroscopy (NMR)Tertiary and quaternary structure> 25 g/l for 50 kDa proteinReal-time application possibleNon-destructiveStructure can be analyzed under native conditionsLarge number of samples necessaryLimited to small proteins (≤ 40 kDa) or protein fragmentsLanucara et al (2014)Kelly et al (2005)Reversed phase high performance liquid chromatography (RP-HPLC)Monitor unfolded proteins and primary structure> 0.3 g/lRapidHigh resolutionRobustHigh temperature during analysis may lead to aggregate formationMere chemical information because proteins are denaturedSturaro et al (2016)Herman et al (2002)Size exclusion high performance liquid chromatography (SE-HPLC)Quantitative protein analysis0.012 g/lNon-destructiveSensitiveNon-denaturating elution conditions possibleLimited dynamic rangeInaccuracy due to alteration of size distributionCodevilla et al (2004)Brusotti et al (2017)Raman spectroscopySecondary structureProtein quantification (SERS)> 1 g/l> 0.08 g/l for SERSSensitive and structural selectiveExpensive equipment (CW-UV laser) and complicated ...…”
Section: Monitoring Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…1.5 g/l for 50 kDa proteinAnalyze and quantify a mixture of proteoforms during folding (e.g. different disulfide bonds)Expensive equipmentInvolatile sample buffers are not compatible with ESI–IMS–MSFuruki et al (2017)Young et al (2016)Extrinsic fluorescenceTertiary and quaternary structureCa. 0.015 g/l for 50 kDa proteinSensitiveSuitable for high-throughput screeningDye might interfere with protein aggregationHawe et al (2008)Younan and Viles (2015)Fourier transform infrared spectroscopy (ATR-FTIR)Secondary structure and dynamics> 0.01 g/lTolerant to salt and sample turbidityCan be used for all proteinsHigh wavelength precisionNo time-related dataPathak et al (2016)Walther et al (2014)Baldassarre and Barth (2014)Nuclear magnetic resonance spectroscopy (NMR)Tertiary and quaternary structure> 25 g/l for 50 kDa proteinReal-time application possibleNon-destructiveStructure can be analyzed under native conditionsLarge number of samples necessaryLimited to small proteins (≤ 40 kDa) or protein fragmentsLanucara et al (2014)Kelly et al (2005)Reversed phase high performance liquid chromatography (RP-HPLC)Monitor unfolded proteins and primary structure> 0.3 g/lRapidHigh resolutionRobustHigh temperature during analysis may lead to aggregate formationMere chemical information because proteins are denaturedSturaro et al (2016)Herman et al (2002)Size exclusion high performance liquid chromatography (SE-HPLC)Quantitative protein analysis0.012 g/lNon-destructiveSensitiveNon-denaturating elution conditions possibleLimited dynamic rangeInaccuracy due to alteration of size distributionCodevilla et al (2004)Brusotti et al (2017)Raman spectroscopySecondary structureProtein quantification (SERS)> 1 g/l> 0.08 g/l for SERSSensitive and structural selectiveExpensive equipment (CW-UV laser) and complicated ...…”
Section: Monitoring Toolsmentioning
confidence: 99%
“…different disulfide bond formation during refolding. ESI–IMS–MS can function as a real-time application to investigate protein folding and may be very useful as a PAT tool (Furuki et al 2017). A disadvantage of ESI–IMS–MS is that involatile buffers (e.g.…”
Section: Monitoring Toolsmentioning
confidence: 99%
“…Overall, we developed a top‐down MALDI‐ISD method for monitoring the status of the disulfide bond of heated lactoglobulin. Additionally, another study has shown that ISD analysis can correlate the free SH by comparing the peak intensity ratio of c ions to precursor ions 26 …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, another study has shown that ISD analysis can correlate the free SH by comparing the peak intensity ratio of c ions to precursor ions. 26…”
mentioning
confidence: 99%